Archaeological excavations at Cockpen medieval parish church, Midlothian, 1993 (Proceedings of the Society of Antiquaries of Scotland, 1996)
Reports excavations in the course of conservation work that revealed the church's structural evolution. Medieval and post-medieval burials were discovered along with indications of pre-church activity. There are details of `Coins and coin-weight' by N M McQ Holmes (898--9).